Survey of cutaneous findings in newborns in Saudi Arabia - Fatimah Budair; Salih Aljabre; Nada Alquorain; Norah Alnafea; Abdullah Aljabre; Abdullah Alburaey (Wolters Kluwer Medknow Publications, 2017)
Background: Skin lesions are commonly observed in newborns. They have been studied in different regions of the world. There are limited reports from Arab countries and they have not been studied in Saudi Arabia. Objective: To determine the occurrence rate of cutaneous findings in Saudi newborns and evaluate their association with maternal and newborn factors. Method: This is a prospective study of cutaneous findings in newborns delivered at King Fahd Hospital of the University between November 2015 and May 2016. Through performing dermatologic examinations, the relationships between the neonatal skin findings and gender, neonatal age, route of delivery, nationality, skin type, maternal age, illnesses, intake of drugs, and consanguinity were statistically evaluated. Results: A total of 313 newborns were included in this descriptive prospective cohort study. Skin findings were found in all the examined infants. The commonest skin finding were Mongolian spot (63.07%) followed by milia (61.34%), erythema toxicum neonatorum (24.92%) and physiological scaling (18.01%). The prevalence of salmon patch was higher in females, milia was more common in newborn examined at the age of 24-48 h. Mongolian spots were more frequent in babies whose mothers were having diabetes mellitus and physiological scaling was more prevalent in newborns whose parents were relatives. Conclusion: All newborns had cutaneous lesions. Skin type, baby gender, nationality and age of the baby at the time of examination were influential factors in congenital melanocytic nevus, linea nigra, salmon patch and milia. Moreover, illnesses during pregnancy and consanguinity had a role on Mongolian spot and physiological scaling occurrences.